Catalytic upgrading of tars generated in a 100 kWth low temperature circulating fluidized bed gasifier for production of liquid bio-fuels in a polygeneration scheme. (1st March 2020) - Eschenbacher, Andreas; Jensen, Peter Arendt; Henriksen, Ulrik Birk; Ahrenfeldt, Jesper; Jensen, Claus Dalsgaard; Li, Chengxin; Enemark-Rasmussen, Kasper; Duus, Jens Øllgaard; Mentzel, Uffe Vie; Jensen, Anker Degn
Graphical abstract: Highlights: Polygeneration of biofuel, char/fertilizer, power and heat. Increasing pyrolysis temperature decreased the yield but improved the bio-oil quality. Catalytic treatment of tars from straw gasification improved bio-oil properties. Significant reduction in acidity and charring tendency of upgrading bio-oils. Minor decrease in energy recovery of bio-oil by the catalytic treatment. Abstract: Gasification of wheat straw, an agricultural residue with high ash content, was investigated in a low temperature circulating fluidized bed (LT-CFB) gasifier in combination with catalytic tar upgrading as a flexible process to co-produce high quality bio-oil, nutrient rich char, and utilize the producer gas for heat and power production. The change in product distribution and bio-oil quality was studied when conducting the catalytic treatment with HZSM-5/γ-Al2 O3 and lower-cost γ-Al2 O3 . The fuel properties of the raw and upgraded bio-oils were analyzed by elemental composition, moisture, total acid number, size exclusion chromatography, basic nitrogen content, gas chromatography–mass spectrometry with flame ionization detection (GC–MS/FID), 1 H nuclear magnetic resonance (NMR), 13 C NMR, and two-dimensional heteronuclear single-quantum correlation (2D HSQC) NMR. The operating temperature of the LT-CFB pyrolysis chamber determined the tar yield and quality in the producer gas. With decrease in pyrolysis temperature from 690 to 570 °C, the tar concentration in the producer gas increased, while the higher heating value of the condensed oil phase decreased from ~35 to 30 MJ/kg and the oxygen content, moisture content, and acidity of the bio-oil increased. Both HZSM-5/γ-Al2 O3 and γ-Al2 O3 were effective catalysts as the tar treatment improved the bio-oil quality in terms of increased heating value and revaporization efficiency, and a reduction in oxygen content, moisture content, total acid number, and basic nitrogen content. Catalytic vapor treatment, e.g. using HZSM-5/γ-Al2 O3 at 500 °C, decreased the energy content in the condensed bio-oil slightly from ~22% to ~20%. The oil quality improved significantly, as the oxygen content (water-free) and TAN of the bio-oil decreased from 13 wt% O and 34 mg KOH/g to 11 wt% O and 3 mg KOH/g, respectively. The catalytically treated bio-oils are thus better suited for further processing in existing oil refineries.